Pemberdayaan Pemuda Generasi Pesona Indonesia Melalui Pelatihan Menulis Konten Instagram Berbahasa Inggris untuk Meningkatkan Promosi Pariwisata di Sulawesi Barat - Kurnia Kurnia; Abdul Wahab; Ratna Ratna; Hamzar Hamzar; Abdul Rajab (I-Com: Indonesian Community Journal, 2024)
GenPI is the implementation of the "go digital" tourism promotion program that is being intensively carried out by the Ministry of Tourism of the Republic of Indonesia as one of Indonesia's tourism marketing strategies, including in West Sulawesi. Instagram content writing training for GenPI administrators is an effort to advance tourism with the hope that promotions through the @genpi_sulbar account will be maximized and have a broader reach to foreign countries. This activity contains 1) forum group discussion; 2) provision of creative writing material; 3) human resource management and social media marketing material; 4) descriptive text and structure material; 5) vocabulary games; 6) introduction to deepl, grammarly and quillbot and 7) mentoring that will always be done through WhatsApp groups and zoom meetings. Based on the results of the Community Service activities that have been carried out, the following conclusions are obtained: 1) partners understand how human resource management and social media marketing, in this case, tourism promotion; 2) Partners understand how the creative process in writing, which includes how to find writing ideas, plan, edit, draft and publish; 3) Partners understand descriptive text material and descriptive text writing structure, 4) Addition of English vocabulary for partners; 5) Partners understand how to use deepl, quillbot and grammarly 6) Partners can write English Instagram captions as tourism promotions.